'Advance care planning, general practitioners and patients: a phase II cluster-randomised controlled trial in chronic life-limiting illness'. Issue Volume 12:Issue e3(2022) (2nd December 2020) - Dierickx, Sigrid; Pardon, Koen; Pype, Peter; Stevens, Julie; Vander Stichele, Robert; Deliens, Luc; De Vleminck, Aline
Abstract : Objectives: Although general practice is an ideal setting for ensuring timely initiation of advance care planning (ACP) in people with chronic life-limiting illness, evidence on the effectiveness of ACP in general practice and how it can be implemented is lacking. This study aims to evaluate feasibility and acceptability of study procedures and intervention components of an intervention to facilitate the initiation of ACP in general practice for people with chronic life-limiting illness. Methods: Pilot cluster-randomised controlled trial testing a complex ACP intervention in general practice versus usual care (ClinicalTrials.gov: NCT02775032 ). We used a mixed methods approach using detailed documentation of the recruitment process, questionnaires and semi-structured interviews. Results: A total of 25 general practitioners (GPs) and 38 patients were enrolled in the study. The intervention was acceptable to GPs and patients, with GPs valuing the interactive training and patients finding ACP conversations useful. However, we found a number of challenges regarding feasibility of recruitment procedures, such GP as recruitment proceeding more slowly than anticipated as well as difficulty applying the inclusion criteria for patients. Some GPs found initiating ACP conversations difficult. The content of the patient booklet was determined to potentially be too complex for patients with a lower health literacy. Conclusion: Although the intervention was well-accepted by GPs and patients, we identified critical points for improvement with regard to the study procedures as well as potential improvements of the intervention components. When these points are addressed, the intervention can proceed to a large-scale, phase III trial to test its effectiveness.